Numerical and experimental investigation of thermal energy storage in a conical finned tube in PCM storage unit / Uday Jad and Abhijeet Shah - Jad, Uday; Shah, Abhijeet (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
In modern world, use of phase change materials (PCMs) in a thermal energy storage system is an efficient way to store the energy. There are many applications of thermal energy storage system in which PCMs is used, namely, heat pumps, solar systems, spacecraft thermal applications etc. The purpose of this paper is to identify effect of geometrical changes on the melting process of PCM. Computational fluid dynamics (CFD) is used to analyze phase change process. Thermal energy storage tank consists of a vertical tube in tube geometry where outer tube consists of phase change material and inner pipe carrying hot fluid. Paraffin is used as latent heat storage material. Further, the paper describes the effect of inlet temperature of heat transfer fluid on the phase change process. Two types of geometries are used, namely cylindrical and conical shaped. Result shows that charging time is 2.56% less for conical shaped storage system rather than the same for cylindrical shaped system. The results of CFD and experimental analysis considering the parameters like flow rate and inlet temperature of heat transfer fluid are compared. The results of the numerical analysis and the experimental readings shows a good agreement between them. It is observed that as the mass flow rate increases, the effectiveness of the PCM based heat exchanger decreases.